Sanitation and Environmental Health in Coastal Areas of Nambo Village, Nambo District, Kendari City, Southeast Sulawesi Province, Indonesia - Andi Fadhilla Rustam; Pitrah Asfian; Puput Monica Rifty; Rina Agustina; Muhammad Bazal M; Fitri Aulia; La Ode Rezamrin; Ayuningtyas Ayuningtyas; Zulfani Indah Lestari; Narti Narti; Kiki Haprianti; Pricilia Riscika; Hestia Ningsih (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2024)
Background: Environmental sanitation aims to achieve clean, healthy, and comfortable living standards for the community. Basic sanitation efforts include managing human waste disposal facilities (latrines), waste management, wastewater drainage systems (SPAL), and adequate provision of clean water. Objective: This study aimed to analyze the factors influencing environmental health among the coastal community in Nambo Village, Nambo District, Kendari City, in 2019. Methods: A descriptive method was employed using secondary data from the 2017 Community-Based Learning (PBL) reports of Halu Oleo University Public Health Faculty students and the 2018 health profile of Nambo Public Health Center. Results: The majority (39%) of residents in Nambo Village used clean water sourced from dug wells. However, 77% did not boil their drinking water before consumption. Ownership of adequate latrines reached 90%, while 68% of wastewater drainage systems (SPAL) did not meet health standards. About 70% of waste disposal sites met proper criteria, but 42% of residents still burned waste as a management method. Additionally, only 36% of houses met the criteria for healthy homes. Conclusion: Environmental sanitation in Nambo Village is generally categorized as moderately good. However, certain indicators, such as SPAL management, drinking water treatment, and healthy home status, do not meet health standards. More intensive efforts are needed to improve the quality of environmental sanitation in Nambo Village. Keywords: Sanitation, Nambo Village, Clean Water, Waste, Latrines, SPAL, Healthy Homes, Kendari